The isolated rocky outcrops of northeastern argentina and their role on the herpetofauna conservation - Piñeiro, Jose Miguel (2021)
Isolated rocky outcrops represent biodiversity centers, refuges for endangered species, and favorable scenarios for endemism. Most studies in these ecosystems have been focused mainly on their flora and secondarily on different groups of animals. To highlight the value of rocky outcrops as ecosystems for biodiversity conservation, in the present study, we describe the diversity of herptiles of three isolated rocky outcrops of northeastern Argentina and compare it with that of other natural areas of the region. We conducted fieldwork from September 2010 to March 2017. We calculated the alpha diversity and the number of rare, threatened and endemic species. For comparative diversity analysis, we calculated the importance of each area for amphibians and reptiles and the beta diversity. Were recorded a total of 56 species (23 amphibians and 33 reptiles), representing 35% of the herptiles recorded for Corrientes province. These species included 19 rare species, seven threatened species, and two endemic species. The overall beta diversity showed considerably differences in species composition between the compared areas. The rocky outcrops showed higher importance for amphibians and reptiles than the other areas studied. Our study contributes to the knowledge of rocky outcrops and highlights their importance in biodiversity conservation.